Hesperetin Nanoparticle Targeting Neutrophils for Enhanced TBI Therapy (Adv. Funct. Mater. 43/2022). (25th October 2022) - Yao, Kai; Mu, Qingchun; Zhang, Yufei; Cheng, Qian; Cheng, Xiaozhi; Liu, Xiaojing; Luo, Chunmei; Li, Chumei; Cai, Shuxia; Luo, Zhicheng; Zhu, Xiulong; Zhang, Xiangtong; et al.
Abstract : Hesperetin Nanoparticles In article number 2205787, Xiangtong Zhang, Liao Cui, Chunming Huang, Longguang Tang, and co‐workers design a hesperetin nanoparticle that targets neutrophils, T‐Hes, catalyzed by myeloperoxidase secreted by neutrophils, which can effectively identify inflammatory neutrophils and quickly gather in the injured area after traumatic brain injury. The sustained release of hesperetin by T‐Hes shows great advantages in anti‐inflammatory treatment, reducing brain edema and improving neurological function.